Nilai-Nilai Pendidikan Akhlak Dalam Novel Ketika Cinta Bertasbih Karya Habiburrahman El Shirazy - Helmi Yanti; Muhammad Saefullah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Morality serves as the fundamental basis for shaping individual character and maintaining social harmony. Moral education is an integral part of the education system, aiming to develop individuals who are faithful, devout, and possess noble character. This study aims to analyze the moral education values contained in the novel Ketika Cinta Bertasbih by Habiburrahman El Shirazy. The research uses a descriptive qualitative method with a library research approach. Primary data is taken from the novel itself, while secondary data comes from supporting references such as books, journals, and scholarly articles. Through the character of Azzam, the novel emphasizes the importance of moral education in relation to God, the Prophet Muhammad, parents, the self, and fellow human beings. The internalization of these values is reflected in attitudes such as gratitude, patience, trust in God, hard work, responsibility, and social awareness. These values are conveyed naturally through the main character’s daily life, making the novel an effective medium for instilling moral and character values, especially among youth. The result is the formation of a religious, resilient, and virtuous character, with a strong emphasis on love grounded in Islamic principles.